THE EFFECTIVENESS OF INTERACTIVE LEARNING APPLICATIONS IN ENHANCING STUDENTS’ ARABIC VOCABULARY MASTERY: A META-ANALYSIS - Andi Indar Wulan; Mardhiana Jamal; Irfan (Tarbiyah Faculty of Ibrahimy University Ibrahimy University, Situbondo, Indonesia, 2026)
This study adopts a quantitative research approach using a meta-analytic method to examine the effectiveness of interactive learning applications in improving students’ Arabic vocabulary mastery. The independent variable is the use of interactive learning applications, while the dependent variable is students’ Arabic vocabulary acquisition. Educational level, class size, and application type were analyzed as moderator variables. The data set consisted of 25 experimental studies published between 2019 and 2025 that met the predetermined inclusion criteria. Data analysis was conducted using Comprehensive Meta-Analysis (CMA) software to calculate the pooled effect size and examine moderator effects. The results indicate a combined effect size of 0.86, categorized as large, with effect sizes ranging from 0.245 to 2.772, most of which fall within the large to very large categories. Moderator analysis revealed no statistically significant differences based on educational level, class size, or application type, although higher effectiveness was observed at the junior and senior high school levels and in gamification-based applications. These findings demonstrate that interactive learning applications have a strong and significant impact on Arabic vocabulary acquisition and provide empirical support for their integration into more effective Arabic language learning strategies.